Beyond the Bump: Reconceiving the Philosophy of Pregnancy - Bianas, Hazel T (Archīum Ateneo, 2021)
French philosopher Hélène Cixous (1976) stressed the importance of feminine writing. She believes that women should take part in sharing their experiences from their own novel points-of-view. We discuss that while pregnancy is an experience unique to women; it has been misappropriated by patriarchal structures throughout the years. The pregnancy bump; which is more than just evidence of the uterus stretching to accommodate the fetus; is a symbol of a woman's triumphs and struggles all throughout conception; pregnancy and childbirth. We show that women have already gone beyond the bump and challenged existing patriarchal systems through different means; as Cixous has enjoined women to do. With this; it is asserted that the philosophy of pregnancy be reconceived as well; in order to escape existing boundaries that constrict the discourse to ethical issues of rape; abortion; and medical interventions; making it face issues that surround women's experience of pregnancy; as well as deeper meanings the pregnant body itself represents.